2021
DOI: 10.3389/fmolb.2021.621963
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Adenosine Diphosphate Stimulates CXCL10-Mediated Mast Cell Infiltration Through P2Y1 Receptor to Aggravate Airway Inflammation in Asthmatic Mice

Abstract: Asthma is an inflammatory disease associated with variable airflow obstruction and airway inflammation. This study aimed to explore the role and mechanism of extracellular adenosine diphosphate (ADP) in the occurrence of airway inflammation in asthma. The expression of ADP in broncho-alveolar lavage fluid (BALF) of asthmatic patients was determined by enzyme linked immunosorbent assay (ELISA) and the expression of P2Y1 receptor in lung tissues was determined by reverse transcription-quantitative polymerase cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…However, the data are different from what we observed upon P2Y 1 deficiency. In previous studies, P2Y 1 blockade and P2Y 1 deficiency did show comparable results (38,77,78), suggesting that the discrepancy we have observed now could be due to sepsis in general or the CLP model. As previous studies investigating either P2Y 1 deficiency or antagonism were performed almost exclusively in male mice (37, 38, 44, 77), our experiments were the first to investigate changes in inflammation levels in sepsis in female mice upon P2Y 1 blockade and compare them with the male counterpart.…”
Section: Discussionsupporting
confidence: 80%
“…However, the data are different from what we observed upon P2Y 1 deficiency. In previous studies, P2Y 1 blockade and P2Y 1 deficiency did show comparable results (38,77,78), suggesting that the discrepancy we have observed now could be due to sepsis in general or the CLP model. As previous studies investigating either P2Y 1 deficiency or antagonism were performed almost exclusively in male mice (37, 38, 44, 77), our experiments were the first to investigate changes in inflammation levels in sepsis in female mice upon P2Y 1 blockade and compare them with the male counterpart.…”
Section: Discussionsupporting
confidence: 80%
“…The M2 polarization of alveolar macrophages correlated with asthma severity in humans, and impaired M2 polarization exhibited less eosinophil recruitment and lung inflammation ( 53 ). The extracellular ADP was enriched in bronchoalveolar lavage fluid of asthmatic patients, and it could aggravate airway inflammation and induce mast cell infiltration in the ovalbumin-induced asthma model ( 54 ). To further investigate the effect of ADP on the inflammatory response, we detected the effect of ADP on macrophage polarization and found that ADP significantly decreased the expression of M1-related proinflammatory cytokines such as IL-6 and TNF-α but increased the expression of M2-related proteins such as CD163 and CD206 in hMDMs.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study showed that ADP—which is a much more potent activation signal for platelets than ATP, is also elevated in asthmatic airways. 115 In turn, activated platelets release a variety of mediators, such as ATP, histamine, serotonin, IL-33, and TxA2, which exert paracrine effects on dendritic cells to promote its maturation and Th2 priming function, and on other immune cells like eosinophils and neutrophils to exacerbate airway inflammation. 116,117 Because SOCE is required for platelet activation, Orai-mediated Ca 2+ signaling can potentially regulate AEC-platelet paracrine cross talk at both ends: by triggering the release of TSLP and IL-33 from AECs and by promoting ADP-mediated Ca 2+ signaling and activation/aggregation of platelets.…”
Section: Epithelial Cell Cross Talk With Immune Cells and The Asmmentioning
confidence: 99%